Innovative coastal zone management : sustainable engineering for a dynamic coast - Schofield, Alexandra (ICE Publishing, 2012)
The world's coastlines play an increasingly important role in energy capture, habitation and the economy, and remain vital for international trade, leisure, recreation, tourism and wildlife. The Institution of Civil Engineers' Coastal Management conference, held in Belfast on 15-16 November, 2011, addressed the modern engineer's role in finding a balance between developmental opportunities, coastal management, and the protection of the physical and social environment. The proceedings of this conference comprise more than 60 peer-reviewed papers presenting current international research and practical applications, highlighting the latest advances and solutions and identifying key areas for further research and debate.